Determinan Pembiayaan Mudharabah Pada Pt. Bank Syariah Mandiri - Rizki Pratiwi Harahap; Putri Bunga Meiliana; Ella Zefriani Lisna (CERED Indonesia Institute, 2023)
The usefulness of this research is for researchers, for IAIN Pdangsidimpuan, and for subsequent researchers. The discussion in this study is related to the field of Islamic banking and business activities of Islamic banks. In connection with this, the theory related to this research is mudharabah financing, profit sharing, capital, and TPF. This research is a quantitative study with multiple linear regression analysis. The data source is secondary data as many as 56 samples. The tests used in this research are descriptive test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, T test, F test, and R2 determination test. The results of the research partially (t test) show that there is no effect for the results on mudharabah financing at PT. Bank Syariah Mandiri, there is no influence of capital on mudharabah financing at PT. Bank Syariah Mandiri, and there is an effect of TPF on mudharabah financing at PT. Bank Syariah Mandiri.